2015
DOI: 10.1016/j.bbrc.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of eNOS in endothelial cells exposed to ionizing radiation involves components of the DNA damage response pathway

Abstract: In this study, the involvement of ataxia telangiectasia mutated (ATM) kinase and heat shock protein 90 (HSP90) in endothelial nitric oxide synthase (eNOS) activation was investigated in X-irradiated bovine aortic endothelial cells. The activity of nitric oxide synthase (NOS) and the phosphorylation of serine 1179 of eNOS (eNOS-Ser1179) were significantly increased in irradiated cells. The radiation-induced increases in NOS activity and eNOS-Ser1179 phosphorylation levels were significantly reduced by treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…There was no difference in the levels of DNA DSB damage induced by ionizing radiation between stem and differentiated cells, indicating that susceptibility to initial damage is independent of differentiation status ( Figure S1 C). Overall, these results are consistent with previous reports observed in various primary and cancer cells ( Fionda et al., 2015 , Nagane et al., 2015 , Oleson et al., 2014 ).
Figure 2 Nitric Oxide Induced Stem Cell Differentiation and DNA Damage Response (A) Partially differentiated cells (d7 EBs) were exposed to the NO donor NOC-18 (5 μM) on days 7, 9, 11, and 13, and the cells were harvested on day 14 for RNA sample analysis by real-time qPCR for NKx2.5.
…”
Section: Resultssupporting
confidence: 94%
“…There was no difference in the levels of DNA DSB damage induced by ionizing radiation between stem and differentiated cells, indicating that susceptibility to initial damage is independent of differentiation status ( Figure S1 C). Overall, these results are consistent with previous reports observed in various primary and cancer cells ( Fionda et al., 2015 , Nagane et al., 2015 , Oleson et al., 2014 ).
Figure 2 Nitric Oxide Induced Stem Cell Differentiation and DNA Damage Response (A) Partially differentiated cells (d7 EBs) were exposed to the NO donor NOC-18 (5 μM) on days 7, 9, 11, and 13, and the cells were harvested on day 14 for RNA sample analysis by real-time qPCR for NKx2.5.
…”
Section: Resultssupporting
confidence: 94%
“…Western blotting was performed as previously described, with some modifications [ 13 ]. For B16F10 and MEF, cells were collected and lysed in modified RIPA buffer (50 mM Tris-HCl [pH 7.4], 150 mM NaCl, 1 mM ethylenediaminetetraacetic acid, 1% NP-40, 0.1% sodium dodecyl sulfate (SDS), 0.1% sodium deoxycholate, and protease inhibitor cocktail) following sonication using a Bioruptor UCD-200 (BM Equipment, Tokyo, Japan) at low intensity for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…NO can be produced by some types of nitric oxide synthases, including neuronal NOS (nNOS), endothelial NOS (eNOS) and iNOS [124]. However, studies have shown that iNOS is primarily responsible for NO production following exposure to IR [125,126]. After exposure to IR, NO can inhibit Ogg1 activity via nitrosylation of the zinc-finger motif of this enzyme [127,128].…”
Section: Inhibition Of Dna Damage Responses Af-ter Exposure To Ir; Stmentioning
confidence: 99%